(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
M-Learning is slowly gaining popularity with the advancement in smartphones cellular technologies namely 4G or Fourth Generation Cellular Networks. M-Learning requires ubiquitous connectivity rich supply of educational materials which should be accessed from anywhere in the world and at any time. Smartphones, tablets, notebooks etc. have become light weight, compact, powerful possess high-definition screens. M-Learning frameworks are needed to upgrade themselves to fully use these devices capabilities to provide rich experience to its users. The study aims to provide the readers with the abridged review of the M-Learning frameworks in the current state. This study will focus only between the year 2009 to the year 2013.